NUMERICAL ANALYSIS OF GEODYNAMIC EVOLUTION OF THE EARTH BASED ON A THERMOCHEMICAL MODEL OF THE MANTLE CONVECTION - Lobkovsky L.I.; Kotelkin V.D. (My University, 2004)
Full-scale numerical modeling of the geodynamic evolution of the Earth throughout its existence is performed in terms of the thermochemical model of mantle convection proposed by the authors. Numerical modelling results are visualized in color and their detailed videorecord is presented. The global geodynamic process is clearly characterized by the presence of cycles of different lengths. Hydrodynamic pulsations associated with reorganizations of convective cells in the upper mantle correlate well with the geological cycles of Stille (~30 Myr). Moreover, the numerical experiments have shown that large avalanche-like flows of substance from the upper mantle into the lower mantle through their endothermic interface took place during the geodynamic evolution of the Earth; these impulsive downward flows significantly differ both quantitatively and qualitatively. In particular, impulsive flows of upper mantle substance into the lower mantle on a continental or regional scale (the so-called avalanches), also observable in our model, correspond in our interpretation to the geological cycles of Bertrand (~170 Myr). In addition, numerical experiments revealed the presence of basically new impulsive flows of upper mantle substance into the lower mantle on a planetary (global) scale that are referred to as overturns; about half of the upper mantle material is replaced by the material of the lower mantle over a relatively short time of the development of such an overturn. In our interpretation, the mantle overturns correlate with the Wilson cycles (700-900 Myr), which is evidence of their geodynamic nature and accounts for such major geological events as periodic assemblages and breakups of continent, the asymmetric structure of the Earth, and others. As the mantle cools during the evolution of the Earth, mantle overturns gradually attenuate and degenerate into mantle avalanches.
Keywords: GEODYNAMIC EVOLUTION; NUMERICAL ANALYSIS; THERMOCHEMICAL MODEL; MANTLE CONVECTION